CompTIA A+ certification all-in-one exam guide (exams 220-901 & 220-902) - Meyers, Mike 1961- (McGraw-Hill Education, 2016)
"This bestselling on-the-job reference and test preparation guide has been fully revised for the new 2015 CompTIA A+ exam objectivesWritten by the leading authority on CompTIA A+ certification and training, this self-study book and CD has been thoroughly updated to cover 100% of the exam objectives on the 2015 CompTIA A+ exams. New topics include managing and maintaining cellular devices, including tablets; configuring operating systems, including Windows 8, Android, and iOS; and enhanced, mobile-centered security and troubleshooting procedures. CompTIA A+® Certification All-in-One Exam Guide, Ninth Edition (Exams 220-901 & 220-902) enables you to take the test with complete confidence. It also serves as a practical reference for IT support and technical personnel. The bonus CD-ROM includes practice exam for both exam 901 and 902 with hundreds of accurate practice exam questions, more than an hour of Mike Meyers training videos, performance based simulations, free PC tools, and a PDF copy of the book. Written with the "in the trenches" voice and clarity Mike Meyers is known for Features pre-assessment tests, exam tips, and "Try This!" sections to reinforce difficult topics Includes a coupon for 10% off of the exam fee, a USD37 value "--
Print version record
Keywords: Microcomputers -- Study guides -- Maintenance and repair -- Examinations; Computer technicians -- Study guides -- Certification; Micro-ordinateurs; Entretien et réparations; Examens; Guides de l'étudiant; COMPUTERS; Certification Guides; A+; Computer technicians; Certification; Microcomputers; Maintenance and repair; Examinations; examination study guides; Study guides; Guides de l'étudiant